Quality of an Ethnomathematics Based Pop-Up Book Media on Fractions for Primary School - Astiningtyas, Sherly Nabila; Trisniawati, Trisniawati; Rhosyida, Nelly; Titi Muanifah, Mahmudah; Widodo, Sri Adi; Agustito, Denik; Rufaidah, Desy; Putu Suardipa, I; Hadi, Windia (RANGE: Jurnal Pendidikan Matematika, 2026)
This research is driven by the urgency of comprehending the basic concepts of fractions found in grade II students. These problems indicate the requirement for enhancing interactive and contextual learning media such as ethnomathematics-based fraction pop-up book media. So, this research aims to see the quality of ethnomathematics-based fraction pop-up book media that is feasible in terms of validity and practicality. This research was performed at SD Negeri 1 Salakan Bantul, with the research subjects being grade II students totalling 22 students. This study uses R&D research using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The data collection techniques used were observation, interview, and questionnaire. The data analysis technique used qualitative and quantitative analysis. The outcomes showed that the ethnomathematics-based fraction pop-up book media met the valid and practical criteria. This can be found in the validation result by media experts and material experts who show "Very Valid" criteria, with a percentage value of media experts of 97.33% and material experts of 93.33%. The assessment was also undertaken regarding the practicality of utilizing the product that showed the criteria ''Very Practical'' by acquiring teacher response scores of 98.67% and students of 98.63%. Based on the data fulfilled, it can be concluded that the ethnomathematics-based fraction pop-up book media is feasible in terms use as an alternative learning media in learning mathematics fraction material in grade II elementary school. Fraction pop-up book media based on ethnomathematics can strengthen comprehension of fraction material by integrating local culture.